Sudden onset hearing loss--causes, investigations and management - Foden, Neil; Mehta, Nishchay; Joseph, Theo (Australian family physician, 2013)
Sudden onset hearing loss (SOHL) has a number of causes, ranging from the simple and reversible to the profound and permanent. The sequelae of a sudden loss of hearing can be significant. This article seeks to address the various aetiologies of SOHL, how they can be diagnosed at the earliest opportunity, and outlines the methods of investigation and management. SOHL causes great concern for the patient. It is when there is a 30 dB or greater hearing loss over less than 72 hours. History and examination, with discerning use of investigations, can identify whether the hearing loss is of conductive or sensorineural origin; and those individuals who have a potentially reversible hearing loss that can be addressed quickly and in an appropriate fashion. However, in the majority of cases of sudden sensorineural hearing loss (SSNHL), no cause is identified and it is considered idiopathic SSNHL. In these patients, high dose oral prednisolone may improve hearing outcome, particularly if started early.